You can treat my HIV - But can you treat my blood pressure? Availability of integrated HIV and non-communicable disease care in northern Malawi - Colin Pfaff; Vera Scott; Risa Hoffman; Beatrice Mwagomba (AOSIS, 2017)
Background: Many patients on antiretroviral therapy (ART) in Malawi have or will develop non-communicable diseases (NCDs). The current capacity of ART sites to provide care for NCDs is not known. Aim: This study aimed to assess the capacity of ART sites to provide care for hypertension and diabetes in rural Malawi. Setting: Twenty-five health centres and five hospitals in two rural districts in northern Malawi. Methods: A cross-sectional survey was performed between March and May 2014 at all facilities. Qualitative interviews were held with three NCD coordinators. Results: Treatment of hypertension and diabetes was predominantly hospital-based. Sixty percent of hospitals had at least one clinician and one nurse trained in NCD care, whereas 5% of health centres had a clinician and 8% had a nurse trained in NCD care. Hundred percent of hospitals and 92% of health centres had uninterrupted supply of hydrochlorothiazide in the previous 6 months, but only 40% of hospitals and no health centres had uninterrupted supply of metformin. Hundred percent of hospitals and 80% of health centres had at least one blood pressure machine, and 80% of hospitals and 32% of health centres had one glucometer. Screening for hypertension amongst ART patients was only conducted at one hospital and no health centres. At health centres, integrated NCD and ART care was more common, with 48% (12/25) providing ART and NCD treatment in the same consultation. Conclusions: The results reflect the status of the initial stages of the Malawi NCD programme at sites currently providing ART care.